The European Research University - Neave, Guy. author. aut Link
XIV, 190 p.
Keywords: In a modern Europe, even with 900 years of history and learning behind it, the European Research University faces major challenges on multiple fronts. This book maps out both the present and the long-term issues that the European Research University must now tackle.